Prevalence of Respiratory Symptoms, Bronchial Asthma and Obstructive Lung Disease among Tannery Workers - Asad Jamall; Atif Mehmood; Fehmida Khatoon; Tuula Putus; Heikki Savolainen; Jyrki Liesivuori (Annals of Environmental Science and Toxicology - Peertechz Publications, 2017)
Objectives: We determined the prevalence of respiratory symptoms, bronchial asthma and obstructive lung disease among selected tannery workers. Method: We conducted a cross-sectional study during 2010-2011 among leather tannery workers in Karachi, Pakistan. The total population of workers in the tannery was 250. A cohort of 160 workers was selected on a convenience sampling basis. Fifty-two controls were selected from the local community. Data was collected through a questionnaire, and lung function tests were carried out by trained professionals to measure FEV1, FVC, PEFR and the FEV1/FVC ratio. Results: Among tannery workers we found whistling symptoms in 20% of the group, awakening from sleep due to a tightness of chest in 23%, diffi culty in breathing in 24%, excessive coughing in 25%, and out of breath on a usual walk in 41%. Among controls, awakening from sleep due to tightness of the chest was 4%, excessive coughing was 4%and shortness of breath during a usual walk was 4%. The prevalence of asthma was 7% in the tannery workers and 4% in the controls. We found obstructive lung diseases in 39.4% of the workers as compared to 11.5% among controls. 64% of the asthmatics considered that their asthma was related to work. A statistically signifi cant relationship was found between bronchial asthma, respiratory symptoms and duration of exposure, smoking, ethnicity and nasal and skin manifestations. Conclusion: The study showed a high prevalence of bronchial asthma, respiratory symptoms and obstructive lung disease among tannery workers, and that it was related to duration of exposure, ethnicity, smoking and nasal and skin allergies.